International students’ views on development, equity, and access in Saudi scholarships under sustainable development goals 4 - Albylwi, Fahad (Journal of International Students, 2026)
This study evaluated the alignment of Saudi Arabia’s international scholarship programs with Sustainable Development Goal 4, with particular attention to the perspectives of international students. It examined students' views on how scholarships contribute to their personal growth and to the development of their home countries. A mixed-methods design combined qualitative data from 60 semistructured interviews, focus groups, and digital ethnographic observations, with quantitative data on regional allocations from official government sources. The findings indicate that students acquired valuable knowledge and skills, but their conceptions of “development” varied by socioeconomic background. Some envisioned returning home to teach, research, or address national challenges, whereas others saw remittances as indirect contributions. Regionally, scholarships are intensely concentrated in Asia and Africa, consistent with SDG 4 equity goals; however, scholarships for Latin America and the Pacific remain limited. Although students described opportunities as broadly inclusive, structural challenges remain.